1990
DOI: 10.1111/j.1748-1716.1990.tb08823.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐linked variation in creatine kinase release, and its dependence on oestradiol, can be demonstrated in an in‐vitro rat skeletal muscle preparation

Abstract: Creatine kinase (CK) release from male and female rat soleus muscles was studied for 4.5 h in vitro, under basal conditions and after electrical stimulation. Basal CK release was greater from male than from female muscles, and CK release from male muscles increased significantly when the muscle tension in the in-vitro set-up was increased. CK release after electrical stimulation was also more marked in male soleus muscles. Pretreatment of male rats and ovariectomized female rats with oestradiol for 3 weeks att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 39 publications
(24 reference statements)
3
38
0
2
Order By: Relevance
“…However, as other investigators have also reported exercise-induced increases in serum CK activity in groups with less than 3 menstrual cycles per year relative to eumenorrheic exercisers [15], it is not unreasonable to think there may be an interactive effect of exercise and hormone status on serum CK activity. Thus, the data presented here are consistent with the finding that CK varies inversely with estrogen levels across menarcheal levels at rest [14], after exercise [15], and corroborate the animal literature on the protective effects of estrogen on the muscle membrane, thereby reducing serum CK activity [40]. Evidence also exists that ovarian steroids increase exercise-induced CK clearance, decreasing serum CK activity [11], perhaps through the modulation of immune cells.…”
Section: Discussionsupporting
confidence: 79%
“…However, as other investigators have also reported exercise-induced increases in serum CK activity in groups with less than 3 menstrual cycles per year relative to eumenorrheic exercisers [15], it is not unreasonable to think there may be an interactive effect of exercise and hormone status on serum CK activity. Thus, the data presented here are consistent with the finding that CK varies inversely with estrogen levels across menarcheal levels at rest [14], after exercise [15], and corroborate the animal literature on the protective effects of estrogen on the muscle membrane, thereby reducing serum CK activity [40]. Evidence also exists that ovarian steroids increase exercise-induced CK clearance, decreasing serum CK activity [11], perhaps through the modulation of immune cells.…”
Section: Discussionsupporting
confidence: 79%
“…Studies in animals support the theory that estrogen protects membrane integrity during times of oxidative stress. Antioxidants act as a cooperative network, employing a series of redox reactions [17][18][19][20]. Additive effect of AsA in anti-oxidation may be responsible for increased levels of tissue estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal studies have reported reduced muscle structural damage and diminished muscle membrane disruption following potentially damaging exercise in rodents when they are exposed to estrogen [6,[25][26][27]. Findings include diminished CK release from muscle, reduced disruption of muscle structural proteins such as dystrophin and desmin and diminished activation of lysosomal enzymes in female rodents or ovariectomized female rodents with estrogen replacement relative to ovariectomized rodents without estrogen replacement [6,28].…”
Section: Positive Effects Of Estrogen On Skeletal Muscle; Mechanisms mentioning
confidence: 99%